Design and Simulation Analysis of Solar-coupled Ground Source Heat Pump System. Issue 1 (September 2020) - Liu, Jiaqi; Liu, Yufeng; Wang, Chengshun; Wang, Chen
Abstract: Solar heating technology and ground source heat pump (GSHP) technology are green technologies which are mainly promoted and applied in our country. Based on the comprehensive analysis of domestic research results on solar energy utilization, GSHP applications and their coupled systems, this paper designs a set of solar-coupled ground source heat pump (SGSHP) system which can operate independently and coupled. Aiming at the characteristics of solar heating and GSHP, the operation mode and control strategy of the system are proposed. Taking a building in Qingdao as an example, the coupled system and the single GSHP system were simulated and analyzed to verify the energy saving advantages of the SGSHP system.